CHANGES IN THE ORAL CAVITY IN ENDOCRINE DISEASES - Norboyev Abdurasul; Abdullayev Nabiyullo; Muratova Saodat Kadirovna (Journal of new century innovations, 2024)
Annotation. One of the problems of modern clinical dentistry is the growth of inflammatory diseases of the oral cavity, occurring against the background of secondary immune deficiency [3,6,8]. An internal factor influencing the immune response is the endocrine system, which is part of the complex of neurocrine regulation of homeostasis. An important role in the etiopathogenesis of various dental diseases is assigned to the complex multi-functional relationships between the immune, nervous and endocrine systems.